2020
DOI: 10.1007/s10295-020-02276-6
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation process for producing CFAs using Yarrowia lipolytica

Abstract: Past research has sought to improve the production of cyclopropane fatty acids by the oleaginous yeast Yarrowia lipolytica by heterologously expressing the E. coli fatty acid synthase gene and improving cultivation processes. Cyclopropane fatty acids display properties that hold promise for biofuel applications. The E. coli fatty acid synthase gene was introduced into several genetic backgrounds of the yeast Y. lipolytica to optimize lipid synthesis; the mean cyclopropane fatty acid productivity was 43 mg L−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Several engineered strains have been generated to over-accumulate specific fatty acids, such as the high oleic acid producing strains, where oleic acid represents more than 90% of the fatty acids [ 53 ], 6.5% of conjugated linoleic acid [ 54 ], Cyclopropane fatty acids reach 22% [ 55 ], 10-methyl branched fatty acids represent 37% [ 56 ] and odd chain fatty acids content was improved from 46.8% up to 62% [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several engineered strains have been generated to over-accumulate specific fatty acids, such as the high oleic acid producing strains, where oleic acid represents more than 90% of the fatty acids [ 53 ], 6.5% of conjugated linoleic acid [ 54 ], Cyclopropane fatty acids reach 22% [ 55 ], 10-methyl branched fatty acids represent 37% [ 56 ] and odd chain fatty acids content was improved from 46.8% up to 62% [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has shown that oftentimes, the impurities in crude glycerol may be an asset in microbial valorization. For example, the production of cyclopropanated fatty acids from crude glycerol in metabolically engineered Y. lipolytica Po1d showed a 2.4-fold increase in titer (7.5 g/l) relative to pure glycerol (Imatoukene et al., 2020 ). However, the specific effect of potential impurities that may explain this was not studied.…”
Section: Other Industrial Wastesmentioning
confidence: 99%
“…2) [49][50][51][52]. When a cell is exposed to acidic or hyperosmotic environment, RpoS induces CFA synthase to cyclise UFA reservoirs into CFA [49,[52][53][54]. CFA synthesis decreases the unsaturation of membranous fatty acid, causing decrease in the membrane fluidity.…”
Section: Stresses Generated Due To Fatty Acid Overproduction Ph and Osmotic Stressmentioning
confidence: 99%